Review on Big Data and Associated Technologies - Yadav, Rimmy; Sharma, Anil (International Journal of Computer Sciences and Engineering, 2025)
Global business, business people, government are generating and consuming vast amount of data very frequently. So in the world of digital computing, it’s become very challenging to deal with this variety and velocity of the data. To overcome these challenges, Big Data is playing an important role by providing, capturing, managing and analyzing these big data sets. Software and technologies of big data facilitates the increase in organizational growth. To know about complete big data, focused has made on the emerging technologies i.e. cloud computing, Internet of Things (IoT) and Hadoop that are closely related to the big data. For each related technology, a description and key features have been highlighted. Finally the authors examined the relationship and benefits among big data and its associate technologies.